Language Errors In Writing Personal Permission Letter Nusa Indah Sdit Students - Wahyuni, Tri; Alwita, Siti (Berpusi Publishing, 2023)
Learning Indonesian aims to improve students' abilities to speak good and correct language. one of them is by observing conditions in a study. Based on initial observations, students often feel difficult and wrong in arranging sentences when asked to write a letter or writing. This research aims to identify and describe the form of syntactic errors, namely writing errors phrases and sentence writing in writing personal letters for class 5 students at SDIT Nusa Indah, hamlet M, Telaga Jernih Village, totaling 13 students. To obtain data What is needed in this research, researchers use observation techniques and test techniques. The data were analyzed using qualitative descriptive methods, namely analyzing data and concluding the results of language error analysis. After the data is analyzed, it can be concluded that there is a syntactic error in the phrase area. There are four forms of errors, namely inappropriate prepositions, inappropriate word order, excessive use of superlative forms, and excessive use or wasteful elements. Next, field usage errors Sentences consist of three forms of errors, namely subject doubling errors, removal of conjunctions, and foreign terms.